The impacts of green human resource management on organisational commitment in Chinese large manufacturing companies - QI, Xinyu (2022)
In recent years, environmental issues have become more serious and the problem of low employee commitment in organisations has become prominent, especially in China. For companies, it is important to consider how HRM can be used to achieve both environmental goals and enhanced organisational commitment. However, current research on Green Human Resource Management (GHRM) is mainly devoted to exploring the impact of the series of HRM approaches on organisations or employees. Therefore, the research aim is to investigate how GHRM affects employees' organisational commitment. This study took large manufacturing enterprises in China as the research target and used a quantitative research method to collect 314 valid questionnaires. Through data analysis, this study finds that green training, green performance management and green involvement have a positive impact on organisational commitment, with green involvement influencing the most. Green pay and rewards affects organisational commitment negatively. Green recruitment and selection does not influence. Gender also moderates the relationship between GHRM and organisational commitment. The research results contribute to the research on GHRM and provide direction for how to implement GHRM in Chinese large manufacturing companies.